Handbook of surface and colloid chemistry - Birdi, K. S., 1934- (CRC Press, 2016)
This new edition of the Handbook of Surface and Colloid Chemistry informs you of significant recent developments in the field. It highlights new applications and provides revised insight on surface and colloid chemistry's growing role in industrial innovations. The contributors to each chapter are internationally recognized experts. Several chapters represent new research areas while others provide updates on important areas of the field. Reduced in length, the new edition presents a more concise volume for quicker understanding of the physical principles necessary for application. It includes.